Respuesta :
Answer:
Option B
Step-by-step explanation:
We have to find the solution to the system of equations
y = 3x² - 8x - 2 ----------------(1)
2x - y = 5
y = 2x - 5 -----------------(2)
Now equate the equations (1) and (2) for the values of y.
3x² - 8x - 2 = 2x - 5
3x² - 8x - 2x - 2 + 5 = 0
3x² - 10x + 3 = 0
3x² - 9x - x + 3 = 0
3x ( x-3 ) - 1 ( x-3 ) = 0
( 3x - 1 ) ( x-3 ) = 0
x = [tex]\frac{1}{3}[/tex] and 3
Now we put x = [tex]\frac{1}{3}[/tex] and 3 in equation (2)
y = 2 × [tex](\frac{1}{3})[/tex] - 5
= [tex]\frac{2-15}{3}[/tex] = [tex]\frac{-13}{3}[/tex]
and y = 3 × 2 - 5
= 6 - 5
= 1
So solutions are [tex](\frac{1}{3}[/tex], [tex]\frac{-13}{3})[/tex] and ( 3, 1 )
Option B is the answer.